Uelen hunters and artists - Bronshtein, Mikhail (Études/Inuit/Studies, 2007)
AbstractUelen is a settlement inhabited by coastal Chukchi and Yupik people who do not only hunt sea animals but also carve their ivory. Archaeological excavations in Uelen testify that ivory carving has existed there at least since the beginning of our era. When whale hunters and traders came in Uelen in the 19th century, traditional ivory carving turned into an ethnic handicraft. In 1931, Uelen residents were the first to open an ivory carving workshop in Chukotka. In the mid-1930s, they benefited from the valuable help of the Russian artist and art critic Alexander Gorbunkov, who encouraged them to develop their own artistic potential. By the end of the 1930s, Uelen carvers and engravers had acquired their particular artistic style based on their deep knowledge of the Arctic hunters’ customs, expressive images of polar animals, and the natural beauty of walrus tusk. The involvement of a large number of Uelen inhabitants in ivory carving was the main reason for its preservation during the Second World War and the difficult aftermath. New tendencies, including human and folklore themes, emerged in the 1950s-1970s alongside traditional hunting depictions. In the 1980s and 1990s, Uelen artists included in their art some patterns from prehistoric ornaments. While many Chukotka artists are using new creative ways in the 2000s, Uelen carvers in general keep closer to tradition. For them, ivory carving has become a symbol of the vanishing culture of their ancestors.